2010
DOI: 10.1007/s00125-010-1958-7
|View full text |Cite
|
Sign up to set email alerts
|

Translationally controlled tumour protein (TCTP) is a novel glucose-regulated protein that is important for survival of pancreatic beta cells

Abstract: Aims/hypothesis This study used proteomics and biochemical approaches to identify novel glucose-regulated proteins and to unveil their role in pancreatic beta cell function. Translationally controlled tumour protein (TCTP) was identified to be one such protein, and further investigations into its function and regulation were carried out. Methods Global protein profiling of beta cell homogenates following glucose stimulation was performed using twodimensional gel electrophoresis. Proteins were identified by mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Interestingly, this paper also reports that glucose deprivation resulted in down-regulation of TCTP, followed by cell death. The latter finding is corroborated by our recent study on pancreatic beta-cells, showing that an exposure to high glucose (25 mM) leads to an increase in intracellular TCTP levels [43]. This paper also demonstrated that overexpression of TCTP partially protects beta-cells against the induction of apoptosis by high levels of saturated fatty acids (palmitate), a particular stress situation for these cells.…”
Section: + -Atpasesupporting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, this paper also reports that glucose deprivation resulted in down-regulation of TCTP, followed by cell death. The latter finding is corroborated by our recent study on pancreatic beta-cells, showing that an exposure to high glucose (25 mM) leads to an increase in intracellular TCTP levels [43]. This paper also demonstrated that overexpression of TCTP partially protects beta-cells against the induction of apoptosis by high levels of saturated fatty acids (palmitate), a particular stress situation for these cells.…”
Section: + -Atpasesupporting
confidence: 82%
“…However, it is likely that this treatment merely reflects a stress condition rather that a genuine nutritional signal. Our recent study on pancreatic beta-cells demonstrated that TCTP levels are subject to glucose regulation in this cell type [43].…”
Section: Cell Physiological Conditions Resulting In Regulation Of Tctmentioning
confidence: 92%
See 1 more Smart Citation
“…Overexpression of TCTP prevented cell death induced by palmitate (Diraison et al 2011). These results imply that TCTP protects β-cells against stress induced by hyperglycaemia and by high concentrations of fatty acids.…”
Section: Metabolic Regulation and Diabetesmentioning
confidence: 53%
“…Furthermore, TCTP ablation arrested cell-cycle progression at the G 1 phase in human pancreatic cancer cells, similar to when the cells were depleted of Pim-3. Diraison and colleagues recently reported that increased TCTP expression reduced the sensitivity of pancreatic b cells to apoptosis (51). We previously observed that Pim-3 shRNA treatment in vitro enhanced the apoptosis of various types of cancer cells (3)(4)(5).…”
Section: Discussionmentioning
confidence: 77%